Regaining the Love of Learning (LEARNing Landscapes, 2010)
This article points to two trends of critical importance for pre-K-12 and postsecondary institutions—the growth of technologies for learning and the need to enhance Indigenous education. With the help of technologies, we must move away from old aspirations of "covering" the curriculum, toward inquiry approaches that help us regain the love of learning. With guidance from the exciting Accord on Indigenous Education drafted by the Association of Canadian Deans of Education, we must transform relations between Aboriginal and non-Aboriginal people across Canada and all educational settings must become beacons of hope for Aboriginal communities.
Keywords: education; k-12; aborginal; curriculum; learning; canada